Lexicons Used in the Bayuh Oton Ritual in Menyali Village - Cantika, Kadek Meisani Dinda; Budasi, I Gede; Rismadewi, Ni Wayan Monik (Universitas Pamulang, 2025)
This study aims to describe the lexicons used in the procedures of the “Bayuh Oton” ritual in Menyali Village, North Bali and describe their cultural meaning. The combination of purification and a traditional Balinese birthday celebration, serves as a cultural practice to cleanse oneself spiritually and physically while honoring ancestral values. Employing a descriptive qualitative approach with an ethnolinguistic perspective, the research are shows there are 29 lexicons embedded in this bayuh oton’s procedures, including terms like mepwacakan (reading an individual's characteristics), natab byakaon (cleansing and purifying oneself from all impurities), and caru tatakan pelukatan (ritual offering used before performing the cleansing process) which reflect the cultural meaning and philosophical teachings of Tri Hita Karana. Data are collected through deep interviews and observations with three selected informants chosen based on a set of specific criteria. This study highlights the role of lexicons in preserving cultural identity amidst the threats posed by language modernization and attrition. This study aims to provide an important contribution to the preservation of the language and culture of Bali. By documenting and analyzing the lexicon in the ritual Bayuh Oton can understand the richness of the Balinese language and develop strategies to preserve it. The results of this research are expected to provide concrete examples of the richness of language integrated with local culture, while also serving as a valuable reference for linguistic and anthropological studies in efforts to preserve existing cultural heritage.